(untitled) - Barnes, J. Wesley (New York, 1994)
Simulation of a finite discrete space. Evaluating factorials, permutations, and combinations. Distributions evaluators. Plotting probability distribtion functions and other univariate functions.
Keywords: Engineering; Statistical methods,Data processing